INOKULASI RIZOBAKTERIA PADA TANAMAN CABAI (Capsicum annum L.) DI TANAH SALIN - Monica Widi anti; Oedjijono Oedjijono; Elly Proklamasiningsih (Fakultas Biologi Universitas Jenderal Soedirman, 2020)
A red chili plant (Capsicum spp.) is one of the horticultural commodities in Indonesia which has good economic value, so it has priority to be developed. Agriculture practices in Java island have partly switched to coastal areas which have characteristics of saline soils. Saline soils are alkaline and nutrient-poor, especially essential nutrients such as P and N. One way to restore fertility in saline soils used beneficial and fertilizing bacteria such as PGPR. Plant growth-promoting rhizobacteria (PGPR) are free-living, soil-borne bacteria, which are capable of enhancing the growth of the plant either directly or indirectly. The objectives of this research were to determain the effect of PGPR isolates to the growth of red chili plants in saline sandy soil and to determine the best PGPR isolate capable to improve the growth of red chili plant in saline sandy soil. The result showed that the inoculation of rhizobacteria significantly affected to plant height and root length of the red chili plant (Capsicum annum). The combination of 3 PGPR isolates (Azospirillum PSA 10, Azotobacter PSA 8, and Marinococcus PSA 1) was the best result in increasing the height and root length of the chili plant (Capsicum annum).